2013
DOI: 10.1016/j.autcon.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management perceptions in construction and design companies

Abstract: Knowledge management (KM) has been studied extensively in recent years. Some consider knowledge to be the most strategically important resource for any company, but the fragmented, project-based and task-oriented nature of construction work makes it more difficult to implement KM in this sector.\ud \ud This paper presents a survey of perceptions of KM implementation in the Spanish construction sector and compares the results obtained from design and construction firms. Data were collected from the leading civi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 29 publications
6
48
0
4
Order By: Relevance
“…Changes in construction projects such as the complexity of projects and construction expertise, the need of tacit knowledge sharing becomes vital, although, organizations are not prompt in effective collection and transferring the embedded learning (Carrillo and Chinowsky, 2006). It has then become very paramour for organizations to use the KM structure to incarcerate and accumulated learning in depositories, embedded learning are difficult to enact, therefore, it becomes vivid to transferred embedded learning in involving workers through social medias Skype, Facebook's, twitter, inbox etc (Forcada et al, 2013). All these apparatuses aid to enable embedded learning transferred instead of packing them inside the storehouses.…”
Section: Knowledge Sharingmentioning
confidence: 99%
“…Changes in construction projects such as the complexity of projects and construction expertise, the need of tacit knowledge sharing becomes vital, although, organizations are not prompt in effective collection and transferring the embedded learning (Carrillo and Chinowsky, 2006). It has then become very paramour for organizations to use the KM structure to incarcerate and accumulated learning in depositories, embedded learning are difficult to enact, therefore, it becomes vivid to transferred embedded learning in involving workers through social medias Skype, Facebook's, twitter, inbox etc (Forcada et al, 2013). All these apparatuses aid to enable embedded learning transferred instead of packing them inside the storehouses.…”
Section: Knowledge Sharingmentioning
confidence: 99%
“…Chen and Mohamed studied the impact of the internal business environment on KM within construction organizations in Hong Kong [11] and also the strategic importance of tacit knowledge management activities in construction [12]. It has been reported that the changes in organizational culture are critical to successful KM [13].…”
Section: Knowledge Management (Km)mentioning
confidence: 99%
“…Graham, et al (2007) discusses four critical stages of management as conception and attainment, knowledge transmission, knowledge clarification and application to oblige organizational goal. On the other hand, Forcada, et al (2013) has drew knowledge formation, knowledge attainment, knowledge distribution and openness to knowledge as the main component of managing knowledge practices. Gold et al (2001) prove that effectiveness of knowledge management process is as a consequence of knowledge substructures, i.e.…”
Section: Research Backgroundmentioning
confidence: 99%